Efektivitas hipnoterapi lima jari pada penurunan masalah kecemasan responden hipertensi - Saputra, Dian angen; Furqoni, Prima Dian; Novikasari, Linawati (JOURNAL OF Mental Health Concerns, 2024)
Abstract   Background: Hypertension is a disorder of the blood vessels which results in the supply of oxygen and nutrients carried by the blood being hampered from reaching the body tissues that need it. Hypertension sufferers who experience anxiety will feel somatic symptoms (symptoms appearing in the body) and feelings of fear or dread. One form of psychotherapy that can be applied to patients who experience hypertension with five anxiety problems is hypnosis therapy. Hypnotic technique is a form of self-hypnosis that can cause a relaxing effect, thereby reducing anxiety and stress from a person's mind. Purpose: To determine the effectiveness of five finger hypnosis therapy on anxiety levels in hypertension sufferers. Method: Descriptive research methods with a care service case study approach were carried out in the management of anxious patients with hypertension, including assessment, diagnosis, intervention, implementation and evaluation. Sampling within the community of Suka Jaya Lempasing Hamlet 03 Batu Menyan was carried out on 2hypertensive patients who experienced anxiety which was managed for one day. Data collection tools include assessment sheets, methods used in interviews and using the Hamilton Rating Scale for Anxiety (HRS-A) questionnaire. Results: This Paper showed that 5 finger hypnosis was effective in reducing anxiety in hypertensive patients. Conclusion: The 5-finger hypnosis innovation intervention can be proven effective in reducing the client's anxiety scale by decreasing the HRS-A score in two hypertensive patients who experience anxiety after the intervention